Meningkatkan Aktivitas Dan Hasil Belajar Muatan Ips Menggunakan Model Pintar Pada Siswa Kelas IV - Noor Liana; Ahmad Suriansyah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This class action research was conducted due to the low activity and learning outcomes of grade IV students at SDN Telawang 3 Banjarmasin. This problem is caused because learning is still one-way, learning resources are still few about problem solving, lack of questions and answers in learning, so that Can lead to lower learning outcomes. For this reason, the authors use a combination of Problem Based Learning (PBL), Number Head Together (NHT) and Scramble models to solve this problem. The research was conducted using quantitative and qualitative methods, with a class action research type, with a 4-session design. The research tools used were observation of teacher activities, observation of student activities, and written tests at the end of each session to find out student learning outcomes. The results showed that student activity increased in each session. In Session 1 and Session 4 assessments, student learning outcomes improved progressively in each session.